Composition-considered Woschni heat transfer correlation: Findings from the analysis of over-expected engine heat losses in a solid oxide fuel cell–internal combustion engine hybrid system. (15th July 2020) - Choi, Wonjae; Song, Han Ho
Abstract: An over-expected amount of heat losses occurred in the internal combustion engine (ICE) of a solid oxide fuel cell (SOFC)–ICE hybrid system and achieving the target efficiency of the hybrid system was seriously impeded by these heat losses. The objectives of this study are to understand the causes of these over-expected heat losses and to propose a new engine heat transfer correlation applicable to engine operation with unconventional fuels, including but not limited to SOFC anode off-gas. First, the effects of composition on the gas convection coefficient were analysed; the engine intake gas in the hybrid system was analysed to have a 1.3–1.4 times larger convention coefficient than general engine intake gas because of its unusual composition. Second, considering the effects of composition, we proposed a new engine heat transfer correlation, named 'composition-considered Woschni'. Third, to validate this new correlation, experiments and simulations of engine operation were conducted while varying the composition of intake gas. The simulation results using the composition-considered Woschni correlation showed much better predictivity than those using the original Woschni correlation. The total root mean square values of the error rates of the main performance indices for all operating conditions decreased from 12.4% to 5.6% by applying this new correlation. Graphical abstract: The 'composition-considered Woschni' correlation proposed in this paper. Image 1 Highlights: Excessive engine heat losses were analysed to be caused by unusual gas composition. The 'composition-considered Woschni' heat transfer correlation was newly proposed. To validate the correlation, experiments and simulations of the engine were conducted. The new correlation showed much improved predictivity for engine performance. The correlation can also be used to simulate engines using other unusual fuels.